O direito à moradia e o direito das crianças e adolescentes à educação e à convivência comunitária: o Residencial Viver Melhor, em Manaus-AM - Vânia Maria do Perpétuo Socorro Marques Marinho (2023)
The thesis deals with the intersection between the right to housing and the rights to education and community living for children and adolescents, focusing on the residents of Residencial Viver Melhor, a development resulting from the Minha Casa, Minha Vida Program in Manaus. The problem to be investigated is whether and, if so, to what extent, there was a lack of proper urban planning and consequent interference with the protection of children's and adolescents' rights, especially to education and community living. The investigation used case study procedures, combined with bibliographical and documentary research and an examination of theoretical references on the topics covered. Data collection consisted of sources from administrative and judicial processes relating to Residencial Viver Melhor, with a due analysis of the relevant legislation. The research concludes that the construction of the housing complex, although it has provided access to housing for its beneficiaries, has generated issues due to the lack of planning to guarantee their other social rights, especially those of children and adolescents. It emphasizes the importance of planning public housing policies that are also committed to the rights of children and adolescents to the city, education and community living.